Causes of the tower crane accidents and safety performance practices at construction site in Malaysia: perspectives from tower crane operator - Muhamad Zaini, Nurmahamira Zairani (2022)
The evolution of the construction industry in this twenty-first century is seen flourishing, with the use of cutting-edge machinery like tower cranes. As a pivotal transportation option and lifting at construction sites, tower cranes are now dominating precedence. The tower crane operations safety and health must be handled carefully to prevent any accidents in order to ensure that the work at the construction site runs briskly. Consequently, this research is conducted to identify the causes of tower crane accidents with the weakness of safety performance practices at a construction site in Malaysia. The research focused on building and civil construction sites around Peninsular Malaysia. Respondents for the research are focusing entirely to tower crane operator as they are the pillar during tower crane operations. The quantitative method was adopted and the data were analysed using Statistical Package for the Social Sciences (SPSS); frequency analysis, descriptive statistics (mean analysis) and correlation coefficient analysis (Spearman analysis). The findings of this research indicate that the major tower crane accident was caused by poor safety management which is tower cranes operated by unskilled and uncertified tower crane operators. Furthermore, respondents have the highest level of agreement for the safety performance implemented on the construction site, with the weaknesses originating from management categories which are the management never provide safety training programs for signalman and tower crane operators. Lastly, the finding of research was selected and integrated into a fishbone diagram, which is a novelty for this research. The establishment of the fishbone diagram was created using empirical data gathered in the field, and as an important tool to recognise the root cause of the problem and weakness of safety performance practices at site. This research also allows authorities and management to have a better understanding of the root causes of accidents, and to help in taking systematic precautions steps to enhance safety performance practices when operating tower cranes. In conclusion, the findings of this research will help further research as well as industry players to mitigate tower crane accidents in Malaysia.